Media and Conflict: Realizing Peaceful Journalism - Said, Irwanti (Jurnal Mercusuar, 2020)
The mass media can’t be separated from the spread of conflict ideas, so that unwittingly in the news can trigger conflict, although some media practitioners often argue that the mass media is not a trigger for conflict. If traced more thoroughly, maybe it is not the media that has the role to start a conflict, but it can foster conflict and continued violence. The problem is that often a story is not packaged properly and without considering its impact on the conflict itself. This research aims to explore the scope of work of a journalist doing his responsibilities in reporting, processing news. One of them is avoiding the portrayal that conflict only consists of two parties fighting on one particular issue. The logical consequence of this kind of description is that there is one party that wins, and there is one party that loses.